(untitled) (AYUSHDHARA, 2022)
One of the most significant branches of Ayurveda is Rasa Sastra, which deals with pharmaceutical preparations made from minerals and plants, such as Kharliya rasayana, Parpati rasayana, Kupipakva rasayana, and Pottali rasayana. One form of Rasa aushadhi, commonly referred to as emergency medicine, is Pottali Rasayana. There are various ways to prepare Pottali Rasayana. Pottali Kalpana is made in a way that is extremely different from other dosage forms, and it offers advantages including a tiny dose, a high potency, ease of handling, and a long shelf life. The specific technique is developed for potentiating the constituents and forming a complex with high therapeutic efficacy. The primary ingredients used in Hemagarbha Pottali Rasa are Suddha Parad, Suddha Gandhak, Tamra Bhasma, and Swarna Bhasma, which is combined with Kumari Swarasa to produce a compact form.